Job Satisfaction Profile in Employees at Kusuma Sahid Prince Hotel Surakarta - Salma, Niken Sofi; Putri, Dhian Riskiana; Purnomosidi, Faqih (GoAcademica Research & Publishing, 2025)
The dynamic rapid development of the modern industrial world makes competition between companies increasingly challenging, with hospitality being one of the industries affected by this rapid development, where one strategy to deal with global economic uncertainty is effective and efficient HR management oriented towards improving productive performance, and as part of this HR management strategy, many contribute to employee productive performance, including job satisfaction. Job satisfaction, its aspects include working conditions, job security, opportunities for growth, salary and communication. This study aims to determine the job satisfaction in employees at Kusuma Prince Hotel Surakarta and understand what affects it. This descriptive qualitative study used purposive sampling to select participants meeting specific research criteria, collecting data through observations and in-depth interviews with hotel employees about their work experiences, documented via audio recordings and photographs. Following data collection, the researchers conducted factor analysis to identify key patterns and themes, ultimately drawing conclusions from the analyzed findings. The study reveals that job satisfaction at Kusuma Sahid Prince Hotel is primarily driven by psychosocial factors like communication and relationships, rather than material benefits. The dynamics of the job satisfaction at Kusuma Sahid Prince Hotel are related to: 1. communication and interpersonal relationships, 2. job security, 3. development opportunities, 4. salary, 5. working conditions. This is demonstrating how human-centered workplace dynamics build organizational strength during economic difficulties.